Diurnal variations of heart rate, urine flow and catecholamine excretion in subjects wearing clothing that provides different thermal insulation. Issue 4 (3rd July 2016) - Park, Shin-Jung; Waterhouse, Jim
Abstract: This study investigated the effects of clothing providing different Clo values upon the circadian rhythm of sympathetic nervous activity, as inferred from urinary catecholamine excretion and heart rate, in a thermoneutral environment. Seven health female subjects were studied for 37.5 h, from 21:00 h on the first day to 10:30 h on the third day, in an isolated climatic chamber controlled at 23.8 ± 0.2 °C and 60 ± 5% RH. Light intensity was 500 lux from 06:30 to 19:30 h, 100 lux from 19:30 to 22:30 h and 0 lux from 22:30 to 06:30 h. Subjects were tested while wearing two different types of clothing: Type L, offering 1.048 Clo of thermal insulation and with the subjects' extremities covered; and Type H, 0.744 Clo of thermal insulation and the subjects' extremities exposed. Urine samples were collected every 4 h, their volumes were measured and they were later assayed for their contents of adrenaline and noradrenaline; the mean heart rate for each of these 4-h periods was also calculated. The daily profiles of the variables were assessed by ANOVA, which indicated that the amplitudes and phases of the daily rhythms differed between the clothing types. This result was examined in more detail by assessing the profiles by single and group cosinor analysis (period = 24 h). All four physiological variables showed clear and statistically significant group cosinor rhythms with both types of clothing. The mean amplitudes of urine flow, the excretion rate of urinary adrenaline and heart rate were greater when wearing Type H rather than Type L clothing ( p  = 0.01 for urine flow and heart rate; p  = 0.072 for rate of excretion of adrenaline). Also, the acrophase of the rate of urinary adrenaline excretion was earlier in all subjects wearing Type H rather than Type L clothing ( p  = 0.048), and the acrophases of urine flow and urinary noradrenaline excretion rate were earlier in six and five of the subjects, respectively. These results show that clothing which is worn in an environment of moderate temperature (23.8 °C) and which offers a lower Clo value (especially if the distal extremities are exposed) might induce an increase in amplitude and/or an advance of acrophase in circadian rhythms of urine flow, excretion of urinary catecholamines and heart rate. It is suggested that these rhythmic changes, which imply changes in the daily profile of sympathetic nervous system activity, might be important when daily thermoregulation and comfort in response to the type of clothing being worn in daily life are considered.